SISTEM PAKAR REKOMENDASI PEMINJAMAN BUKU DI PERPUSTAKAAN SEKOLAH TINGGI TEKNOLOGI ADISUTJIPTO YOGYAKARTA DENGAN METODE PENYARINGAN KOLABORATIF - Hasibuan, Piniel Romulia; Honggowibowo, Anton Setiawan; Wintolo, Hero (Compiler, 2012)
Library of Sekolah Tinggi Teknologi “Adisutjipto” Yogyakarta has developed rapidly according to the world development and the increasing number of library members and book collections that are owned by the library. The billing system which is running now is able to serve books borrowing and returning services to the members, but is unable to provide an alternative book recommendation according to a certain book borrowed by a member. Book Recommendation Expert System for Library of Sekolah Tinggi Teknologi “Adisutjipto” Yogyakarta with collaborative filtering method uses historic book borrowing data, building, and maintaining profiles of the members of library based on the major taken by the member and the favourite reading topic of each member in order to provide some alternatives when a member borrow a book. After passing the test period, this system is claimed effective to be used in the library, make the library service become more efficient in providing alternative book recommendations, and is able to provide user satisfied alternative book recommendations.